PERAN FAKTOR VIRULENSI PADA PATOGENESIS INFEKSI Candida albicans - Pujiana Endah Lestari (Fakultas Kedokteran Gigi Universitas Jember, 2010)
Candida albicans infection is a fungal infection that most often encountered in the clinic and often recurrent. C. albicans infection remains a significant clinical problem. C. albicans can cause severe infection in mucosal and systemic, especially in patients with immunological disorders. Pathogenesis of C. albicans infection through the development of the virulence factors and specific strategies for success in colonization, infection of thehost tissue. The purpose of this paper is to describe the role of virulence factors in pathogenesis of C.albicans infection. In C. albicans infection, the role of virulence factors are very important, in addition to the role of an impaired immune status. Some virulence factors involved in infection of C. albicans are phenotypic switching, dimorfims morphology, adhesion, secretion of hydrolytic enzymes and others.